Burkholderia pseudomallei: First case of melioidosis in Portugal. (2016) - Pelerito, Ana; Nunes, Alexandra; Coelho, Susana; Piedade, Cátia; Paixão, Paulo; Cordeiro, Rita; Sampaio, Daniel; Vieira, Luís; Gomes, João Paulo; Núncio, Sofia
Abstract: Burkholderia pseudomallei is a Gram-negative bacillus and the causative agent of melioidosis, a serious infection associated with high mortality rate in humans. It can be naturally found as an environmental saprophyte in soil or stagnant water, and rice paddies that predominate in regions of endemicity such as Northeast Thailand. B. pseudomallei is a Biosafety Level 3 organism due to risks of aerosolization and severe disease and is now included in formal emergency preparedness plans and guidelines issued by various authorities in the United States and Europe. Here, we report the first case of imported melioidosis in Portugal. B. pseudomallei was isolated from the patient's blood as well as from a left gluteal abscess pus. The isolate strain showed the unusual resistance profile to first-line eradication therapy trimethroprim/sulfamethoxazole. Whole genome sequencing revealed its similarity with isolates from Southeast Asia, suggesting the Thai origin of this Portuguese isolate, which is in agreement with a recent patient's travel to Thailand.